1998
DOI: 10.1016/s0370-2693(98)01433-6
|View full text |Cite
|
Sign up to set email alerts
|

New excitations in the Thirring model

Abstract: The quantization of the massless Thirring model in the light-cone using functional methods is considered. The need to compactify the coordinate x − in the light-cone spacetime implies that the quantum effective action for left-handed fermions contains excitations similar to abelian instantons produced by composite of left-handed fermions. Righthanded fermions don't have a similar effective action. Thus, quantum mechanically, chiral symmetry must be broken as a result of the topological excitations. The conserv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In [5] we showed that for the Thirring model in the light cone, the composite L −L dx − ψ † L ψ L is quantized and we argued also that this quantization is due to S 1 × ℜ topology induced by the light cone frame. In this section we will show that this quantization rule is quite natural and it is always present in the quantization of physical systems when periodic or antiperiodic boundary conditions are assumed.…”
Section: A Quantum Mechanical Examplementioning
confidence: 81%
See 3 more Smart Citations
“…In [5] we showed that for the Thirring model in the light cone, the composite L −L dx − ψ † L ψ L is quantized and we argued also that this quantization is due to S 1 × ℜ topology induced by the light cone frame. In this section we will show that this quantization rule is quite natural and it is always present in the quantization of physical systems when periodic or antiperiodic boundary conditions are assumed.…”
Section: A Quantum Mechanical Examplementioning
confidence: 81%
“…On the other hand a quantization condition similar to the flux quantization condition found in [5] for the Thirring model can be derived directly from the equation of motion for the fermion variable ψ…”
Section: A Quantum Mechanical Examplementioning
confidence: 95%
See 2 more Smart Citations
“…In this article we review some recent results previously reported in [1,2], where a new type of nonperturbative excitations was identified in the Thirring and Schwinger models.…”
mentioning
confidence: 80%